PERAN AL-QUR'AN DALAM MEMBANGUN HUBUNGAN HARMONIS ANTARA ANAK DAN ORANG TUA - Anisa Cantika; Ali Akbar; Syahruddin Srg; Fauzan Azima Syafiuddin (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This research aims to explore the role of the Qur'an in building a harmonious relationship between children and parents within the Islamic community. A harmonious family relationship is an important foundation in creating social and psychological well-being, especially in Muslim communities that regard the Qur'an as a guide for life. Through a qualitative approach, this study employs in- depth interviews and participatory observation with several Muslim families in a specific Islamic community. The collected data were analyzed using thematic analysis techniques to identify Qur'anic values applied in the relationship between children and parents. The research findings show that the teachings of the Qur'an, particularly those related to respect for parents, patience, compassion, and good communication, play a significant role in shaping positive interactions between children and parents. Respondents also emphasized the importance of instilling moral and spiritual values early on to maintain family harmony. Moreover, the practice of Qur'anic teachings in daily life has been proven to strengthen emotional bonds and improve the quality of communication within the family. In conclusion, the Qur'an serves as a primary guide in creating harmonious relationships between children and parents in the Islamic community. This study provides important contributions to understanding how Qur'anic values can be implemented in family practices to achieve a more peaceful and prosperous life, and it offers implications for family policy development in the context of education and religious guidance.